Hyaluronan regulates sperm-induced inflammatory response by enhancing sperm attachment to bovine endometrial epithelial cells via CD44: in-silico and in-vitro approaches - Ezz, Mohamed Aboul; Mansouri, Alireza; Akthar, Ihshan; Yousef, Mohamed Samy; Kowsar, Rasoul; Miyamoto, Akio (Frontiers in Endocrinology, 2023)
Recently, we reported that sperm induce cluster of differentiation 44 (CD44) expression and Toll-like receptor 2 (TLR2)-mediated inflammatory response in bovine uterus. In the present study, we hypothesized that the interaction between CD44 of bovine endometrial epithelial cells (BEECs) and hyaluronan (HA) affects sperm attachment and thereby enhancing TLR2-mediated inflammation. To test our hypothesis, at first, in-silico approaches were employed to define the binding affinity of HA for CD44 and TLR2. Further, an in-vitro experiment using the sperm-BEECs co-culture model was applied to investigate the effect of HA on sperm attachment and inflammatory response. Here, low molecular weight (LMW) HA at different concentrations (0, 0.1, 1, or 10 µg/mL) was incubated with BEECs for 2 h followed by the co-culture without- or with non-capacitated washed sperm (106/ml) for additional 3 h was performed. The present in-silico model clarified that CD44 is a high-affinity receptor for HA. Moreover, TLR2 interactions with HA oligomer (4- and 8-mers) target a different subdomain (h-bonds) compared to TLR2-agonist (PAM3) which targets a central hydrophobic pocket. However, the interaction of LMW HA (32-mers) with TLR2 revealed no stability of HA at any pocket of TLR2. Notably, the immunofluorescence analysis revealed the HA localization in both endometrial stroma and epithelia of ex-vivo endometrial explant. Moreover, ELISA showed significant levels of HA in BEECs culture media. Importantly, BEECs pretreatment with HA prior to sperm exposure increased the number of attached sperm to BEECs, and upregulated the transcriptional levels of pro-inflammatory genes (TNFA, IL-1B, IL-8, and PGES) in BEECs in response to sperm. However, BEECs treated with HA only (no sperm exposure) did not show any significant effect on the transcript abundance of pro-inflammatory genes when compared to the non-treated BEECs. Altogether, our findings strongly suggest a possible cross-talk between sperm and endometrial epithelial cells via HA and HA binding receptors (CD44 and TLR2) to induce a pro-inflammatory response in bovine uterus.